A case of Wohlfahrtiimonas chitiniclastica bacteremia in continental United States - Chavez, Jesus A. (JMM Case Rep, 2017)
INTRODUCTION: Wohlfahrtiimonas chitiniclastica has been associated with open wound infections, cellulitis, osteomyelitis, and bacteremia. CASE PRESENTATION: We report the case of a 41 year old woman with history of congenital myelomeningocele, paraplegia and extensive decubitus ulcers that developed W. chitiniclastica bacteremia secondary to an infected ulcer. CONCLUSION: W. chitiniclastica is an emerging human pathogen that can be readily identified by MALDI-TOF or sequencing.